Caracterização tectono-estratigráfica integrada de reservatórios do pós-sal na porção sudoeste da Bacia de Campos - Habermann, Leonardo [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The subject of the present work consists in the tectonic-stratigraphic evaluation of eight oil fields located in the southwestern portion of the Campos Basin, where the first offshore production wells were drilled in Brazil. Until 1981, the oil fields of Enchova, Linguado and Pampo, located in the study area of this work, already constituted commercial oil fields in Brazilian waters, revealing the importance of this region to the national exploratory context. The recent fall in production of important reservoirs in the basin, like the turbidites of the Paleogene, makes of paramount importance studies of regional character, wich allow the ample understanding of the mechanisms acting in the generation of the hydrocarbon accumulations present in the region. In this context, the present study aims at the integrated tectono-stratigraphic characterization of the main reservoirs in the Albian-Eocene range, by means of the analysis and correlation of 34 well profiles, in addition to the interpretation of 62 2D seismic lines and two 3D seismic volumes, which totalize an area of 140 km². The elaborated stratigraphic sections allowed to characterize the sedimentation of the post-rifte and drift phases in the studied area, allowing the identification of the main local production intervals: calcarenitic rocks in the upper portion of the Quissamã Formation and Cretaceous and Eocene turbidites of the Carapebus Formation, these last sudvided into two specific levels (EO-01 and EO-02). The seismic data interpreted, in association with structural and isopach maps, were used for the characterization of the structural and stratigraphic mechanisms acting in the formation of the petroleum accumulations described. It was observed the predominance of structural traps in the carbonates of Pampo, Linguado and Bicudo fields, while in Enchova ... (Complete abstract electronic access below)

O alvo de estudos do presente trabalho consiste na avaliação tectono-estratigráfica de oito campos petrolíferos situados na porção sudoeste da bacia de Campos, área onde foram perfurados os primeiros poços offshore produtores no Brasil. Até o ano de 1981, os campos de Enchova, Linguado e Pampo, localizados na área de estudos deste trabalho, já constituíam campos petrolíferos comerciais em águas brasileiras, revelando a importância desta região ao contexto exploratório nacional. A recente queda na produção de reservatórios importantes na bacia, a exemplo dos turbiditos do paleógeno, torna de suma importância estudos de caráter regional, que permitam a compreensão ampla dos mecanismos atuantes na geração das acumulações de hidrocarbonetos presentes na região. Neste contexto, o presente estudo visa à caracterização tectono-estratigráfica integrada dos principais reservatórios existentes no intervalo Albiano - Eoceno, por meio da análise e correlação de perfis de 34 poços, além da interpretação de 62 linhas sísmicas 2D e dois volumes sísmicos 3D, que totalizam 140 km² em área. As seções estratigráficas elaboradas permitiram caracterizar a sedimentação das fases pós-rifte e drifte em meio à área estudada, possibilitando também a identificação dos principais intervalos produtores locais: rochas calcareníticas na porção superior da Formação Quissamã e turbiditos cretácicos e eocênicos da Formação Carapebus, estes últimos subdivididos em dois níveis específicos (EO-01 e EO-02). Os dados sísmicos interpretados, em associação aos mapas estruturais e de isópacas gerados, foram utilizados para a caracterização dos mecanismos estruturais e estratigráficos atuantes na formação das acumulações petrolíferas descritas. Constatou-se a predominância ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Geologia estratigráfica; Carbonatos; Turbidito; Trapas estratigráficos (Geologia do petróleo); Campos, Bacia de (RJ)